2020
DOI: 10.3390/land9100386
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impacts of Soil Tillage System on Isoflavone Concentration of Soybean as Functional Food Ingredients

Abstract: Soybean is an important natural source of isoflavones, but their concentration is likely to be influenced by external factors, such as climatic conditions and soil tillage systems. However, there is minimal information about the effects of such external factors on the isoflavone concentration in soybeans grown in Europe. Therefore, in this study, field experiments were established in Romania to investigate the potential impacts of three different soil tillage systems—conventional, minimum tillage and no-tillag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…They contain a wealth of different ingredients, e.g., dietary fiber and crude protein, but probably one of the most valuable is genistein [ 35 , 36 ]. It is worth emphasizing that the content of genistein in soybeans is not influenced by the soil tillage system [ 37 ], while the technological processing of soybeans has a significant effect on this parameter. Okara (soybean waste from soymilk extraction) contains considerable amounts of isoflavones represented by genistein, with a content of 2.15 mg/100 g [ 38 ].…”
Section: Fermentation As a Way To Increase Genistein Contentmentioning
confidence: 99%
“…They contain a wealth of different ingredients, e.g., dietary fiber and crude protein, but probably one of the most valuable is genistein [ 35 , 36 ]. It is worth emphasizing that the content of genistein in soybeans is not influenced by the soil tillage system [ 37 ], while the technological processing of soybeans has a significant effect on this parameter. Okara (soybean waste from soymilk extraction) contains considerable amounts of isoflavones represented by genistein, with a content of 2.15 mg/100 g [ 38 ].…”
Section: Fermentation As a Way To Increase Genistein Contentmentioning
confidence: 99%
“…The Felix soybean variety was created from the early Maple Presto x Merit varieties that originated in North America [8]; it has very good characteristics, is productive, is resistant to falling and shattering, and has a short vegetation period (making it possible to be harvested in mid-September) [7,8], thus making it a very good precursor for other crops [9,10]. An increase in interest in soybean crop is expected in the coming years [11,12], making it the main source of protein and oil worldwide [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Potassium is the most common element in plant tissue; it plays a key role in regulating cellular osmotic potential and activates over 60 enzymes mainly involved in the synthesis of sugars, starches, and proteins [15,29]. However, many authors have reported that high yields with superior quality indices are given both by genetic development and sustainable management practices [8,24,29].…”
Section: Introductionmentioning
confidence: 99%
“…Soybean production is affected by soil fertility and soil water content in relation to the soil tillage system [26][27][28], and the quality of soybean production is affected more by fertilization and climatic factors [29].…”
Section: Introductionmentioning
confidence: 99%